Test-retest reliability of isometric mid-thigh pull maximum strength assessment: a systematic review - Grgic, Jozo; Scapec, Bela; Mikulic, Pavle; Pedisic, Zeljko (Biology of Sport, 2022)
The aim of this systematic review was to explore the test-retest reliability of isometric mid-thigh pull maximum strength assessment. We searched through five databases to find studies that examined the testretest reliability of peak force in the isometric mid-thigh pull exercise. From each included study, we extracted intra-class correlation coefficients (ICC) and/or coefficient of variation (CV). The methodological quality of the included studies was evaluated using the COSMIN checklist. A total of 16 good-to-excellent quality studies were included in the review. When considering results from all included studies, ICCs ranged from 0.73 to 0.99 (median ICC = 0.96), where 78% of ICCs were ≥ 0.90, and 98% of ICCs were ≥ 0.75. The range of reported CVs was from 0.7% to 11.1% (median CV = 4.9%), where 58% of CVs were ≤ 5%. Reliability was also good-to-excellent for both relative and absolute peak force and for both bilateral and unilateral isometric mid-thigh pull tests. The majority of studies did not find significant differences between testing sessions. It can be concluded that the isometric mid-thigh pull maximum strength assessment has good-to-excellent test-retest reliability. The isometric mid-thigh pull maximum strength assessment can be used as a reliable test in sports practice and for research purposes.